On a programmable approach to introducing digital design - Nixon, M.S. (IEEE transactions on education, 1997)
Introductory approaches to digital design have traditionally centered on small-scale integration as the implementation technology. An approach which centers on programmable logic devices is now much more appropriate given their widespread adoption by industry. This can support all standard concepts in combinational and sequential design with the advantage of introducing a technology now standard for implementation. Programmable array logic (PAL) technology appears most suited to an introductory approach since it is low-cost with clear extension to advanced programmable logic techniques; there are many PAL specification (programming) systems and many PAL devices available. There is no ideal "educational" PAL since commercial design is a compromise of great complexity. A review of several systems which can be used to specify PAL interconnect (covering PALASM, PLPL, PLACE, ABEL-SE, and MAX+PLUS II) shows that all can support an introductory course, that there is limited standardization, and that there are a number of advantages offered by the more sophisticated packages. Using a programmable approach implies that the academic curriculum can be revised for a new implementation. Such revision is not new in a subject which has demonstrated awesome progress in its short history. The time is now right for programmable logic to give a new interpretation into the appropriate concepts for introducing students to digital design.